Amazing Grace - Hoffman, Mary, 1945-; Binch, Caroline (New York, NY : Dial Books for Young Readers, 2016)
Although a classmate says that she cannot play Peter Pan in the school play because she is black, Grace discovers that she can do anything she sets her mind to do.
Accelerated Reader AR
Keywords: African Americans -- Juvenile fiction